Australia A Cultural History - Rickard, John (Australian History, 2017)
Australia: A Cultural History, first published in 1988, is still the only short history of Australia from a cultural perspective. It has acquired a unique reputation as an introduction to the development of Australian society and was listed by the historian and public intellectual John Hirst in his 'First XI: The best Australian history books'. The book focuses on the transmission of values, beliefs and customs amongst the diverse mix of peoples who are today's Australians. The story begins with the 60,000 years of the Aboriginal presence and their continuing material and spiritual relationship with the land, and takes readers through the turbulent years of British colonisation and the emergence, through prosperity, war and depression, of the cultural accommodations which have been distinctively Australian. This 3rd Edition concludes with a critical review of the challenges facing contemporary Australia and warns that 'we may get the future we deserve'. [Some images unavailable for OA]